Regulatory elements in eIF1A control the fidelity of start codon selection by modulating tRNA(i)(Met) binding to the ribosome - Saini, Adesh K. (Cold Spring Harbor Laboratory Press, 2010)
eIF1A is the eukaryotic ortholog of bacterial translation initiation factor IF1, but contains a helical domain and long unstructured N-terminal tail (NTT) and C-terminal tail (CTT) absent in IF1. Here, we identify elements in these accessory regions of eIF1A with dual functions in binding methionyl initiator tRNA (Met-tRNA(i)(Met)) to the ribosome and in selecting AUG codons. A pair of repeats in the eIF1A CTT, dubbed Scanning Enhancer 1 (SE(1)) and SE(2), was found to stimulate recruitment of Met-tRNA(i)(Met) in the ternary complex (TC) with eIF2·GTP and also to block initiation at UUG codons. In contrast, the NTT and segments of the helical domain are required for the elevated UUG initiation occurring in SE mutants, and both regions also impede TC recruitment. Remarkably, mutations in these latter elements, dubbed scanning inhibitors SI(1) and SI(2), reverse the defects in TC loading and UUG initiation conferred by SE substitutions, showing that the dual functions of SE elements in TC binding and UUG suppression are mechanistically linked. It appears that SE elements enhance TC binding in a conformation conducive to scanning but incompatible with initiation, whereas SI elements destabilize this conformation to enable full accommodation of Met-tRNA(i)(Met) in the P site for AUG selection.